The effect of the application of the project-based learning model assisted by pop up book media on the creative thinking ability of elementary school students - Zahra Wardatul Janah; Afridha Laily Alindra; Teten Ginanjar Rahayu (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the improvement of the creative thinking skills of elementary school students through the application of the Project Based Learning (PjBL) model assisted by Pop Up Book media in science learning water cycle materials. The research uses a quasi-experimental method with a Non-Equivalent Control Group Design. The research sample amounted to 50 students in class V of SDIT Almanar Purwakarta which were divided into experimental classes and control classes. Data were collected through a creative thinking ability test and analyzed using a simple linear regression test, Independent Sample t-test, and N-gain. The results of the study showed that the PjBL model assisted by Pop Up Book media had a significant effect on students' creative thinking skills (sig. 0.045 < 0.05). There was a significant difference in the improvement in creative thinking skills between the experimental class and the control class (sig. 0.000 < 0.05). The average posttest score of the experimental class was 86.25, higher than the control class of 60.72. The N-gain result of the experimental class was 0.689 (medium category), while the control class was 0.358. The findings of the study show that the PjBL model assisted by Pop Up Book media can be an effective learning alternative to improve students' creative thinking skills in science learning in elementary school.